2019
DOI: 10.3390/ijms20225580
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergies and Ageing

Abstract: All over the world, there is an increase in the overall survival of the population and the number of elderly people. The incidence of allergic reactions is also rising worldwide. Until recently, allergies, and in particular food allergies (FAs), was regarded as a pediatric problem, since some of them start in early childhood and may spontaneously disappear in adulthood. It is being discovered that, on the contrary, these problems are increasingly affecting even the elderly. Along with other diseases that are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 77 publications
0
34
0
14
Order By: Relevance
“…However, the current exponential growth of the adult and elderly population, especially in Western countries, and the environmental and lifestyle changes, have profoundly changed the epidemiology of FA with a growing increase even in advanced age. Moreover, FA in aging exhibits peculiar clinical features and immunopathogenetic mechanisms, increasing the diagnostic complexity [14].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current exponential growth of the adult and elderly population, especially in Western countries, and the environmental and lifestyle changes, have profoundly changed the epidemiology of FA with a growing increase even in advanced age. Moreover, FA in aging exhibits peculiar clinical features and immunopathogenetic mechanisms, increasing the diagnostic complexity [14].…”
Section: Epidemiologymentioning
confidence: 99%
“…Other cytokines, including thymic stromal lymphopoietin (TSLP) and IL-33, reprogram the APCs, transforming them into cells capable of shifting the differentiation of naive lymphocytes towards IL-4 and IL-13, producing Th2 cells rather than Tregs, with consequent allergic sensitization [94,95]. Inflammation, favored by the age-related gut barrier and digestive function impairment, as well as by the chronic inflammation that characterizes senescence, plays a central role in the breakdown of tolerance to food antigens in the elderly [14,96,97].…”
Section: Tolerance Disruptionmentioning
confidence: 99%
“…Sex, age, psychological and socio-economic factors influence the developing and the manifestations of these disorders. IgE-mediated such as oral allergic syndrome and digestive anaphylaxis and non-IgE-mediated such as eosinophilic disorders and food protein induced enterocolitis syndrome food allergies are described and represent an increasing public health concern [68][69][70][71]. It is recognized the association of food allergy with some congenital immunodeficiency syndromes.…”
Section: Food Allergymentioning
confidence: 99%
“…In their meta-analysis including 16 studies with a total of 956 patients (both adults and children), Yuan et al concluded that H. pylori eradication could resolve IDA [80]. The pathogenesis of IDA related to H. pylori is not fully known [79], and various mechanism have been proposed: chronic gastrointestinal bleeding due to gastric mucosa erosions, the use of iron by bacteria for growth and proliferation, a reduced concentration of ascorbic acid in the gastric juices, and the upregulation of proinflammatory cytokines and hepcidin (a key regulator of iron homeostasis) [69,77,79,[81][82][83][84]. In vitro studies have shown that iron-repressible outer membrane proteins are expressed by H. pylori and could be involved in heme binding and/or uptake [85].…”
Section: Other Causes Of Iron Deficiency Anemia In Celiac Patientsmentioning
confidence: 99%